Analisis Efektivitas dan Kontribusi Penerimaan Pajak Restoran Dalam Upaya Meningkatkan PAD Kabupaten Bandung Barat - Fajar Ramadan; Sudjana; Etti Ernita Sembiring (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
To increase LGR, the Government of West Bandung Regency has made various efforts that focus on tax sector revenue, especially from restaurant tax which has increased its potential and revenue every year. However, there are several problems and some restaurant tax category does not reach the target. The research method used quantitative descriptive with effectiveness analysis and contribution analysis, and qualitative descriptive with interactive model data analysis by Miles and Huberman. Collecting data through interviews, documentation and observation. The data used are SSPD recapitulation, LRA and other supporting data. The results showed the overall effectiveness level and the restaurant category were very effective because they exceeded 100%, but for other categories was still less effective because it was below 80%. The level of restaurant tax contribution to PAD each year is still very low because it is below 6%. Inhibiting factors for restaurant tax revenue include internal factors (lack of human resources) and external factors (derived from taxpayers). Efforts to overcome these problems include optimization of human resources, intensification and extensification, implementation of socialization, imposition of sanctions, billing involving third parties and checkers, as well as special agreements with certain taxpayers.